Pengaruh orientasi religiositas terhadap perfeksionisme maladaptif pada mahasiswa - Loveilia Geovani; Yonathan Aditya (Jurnal Psikologi Ulayat, 2021)
Several studies have found that religion linked to perfectionism can harm mental health. Conversely, most research found that religion resulted in positive effects on mental health. Therefore, the current study was conducted to better understand this phenomenon by examining religious orientation's influence on maladaptive perfectionism among 82 college students with high levels of perfectionism as indicated by the designated instrument. The data was subject to parametric statistical analysis using Pearson Product-Moment correlation and multiple linear regression. The results showed that intrinsic religious orientation negatively influences maladaptive perfectionism, while extrinsic religious orientation positively influences maladaptive perfectionism. The study highlights the importance for college students to develop an intrinsic religious orientation to achieve an adaptive perfectionism.